Mechanism of Earthquake Simulation as a Prenatal Stressor Retarding Rat Offspring Development and Chinese Medicine Correcting the Retardation: Hormones and Gene-Expression Alteration. (26th November 2012) - Zhang, X. G.; Zhang, H.; Tan, R.; Peng, J. C.; Liang, X. L.; Liu, Q.; Wang, M. Q.; Yu, X. P.
Abstract : We aimed to investigate the mechanism of shaking as a prenatal stressor impacting the development of the offspring and Chinese medicines correcting the alterations. Pregnant rats were randomized into earthquake simulation group (ESG), herbal group (HG) which received herbal supplements in feed after shaking, and control group (CG). Findings revealed body weight and open field test (OFT) score of ESG offspring were statistically inferior to the CG and HG offspring. The corticosterone levels of ESG were higher than those of CG but not than HG. The dopamine level of ESG was slightly lower than that of the CG and of HG was higher than that of ESG. The 5-HT of ESG was higher than CG and HG. The growth hormone level of the ESG was significantly lower than ESG but not than CG. Gene expression profile showed 81 genes upregulated and 39 genes downregulated in ESG versus CG, and 60 genes upregulated and 28 genes downregulated in ESG versus HG. Eighty-four genes were found differentially expressed in ESG versus CG comparison and were normalized in ESG versus HG. We conclude that maternal shaking negatively affected physical and nervous system development, with specific alterations in neurohormones and gene expression. Chinese herbal medicine reduced these negative outcomes.